Fine-Scale Monitoring of Routine Deep Dives by Gravid Leatherback Turtles during the Internesting Interval Indicate a Capital Breeding Strategy - Okuyama, Junichi; Seminoff, Jeffrey A.; Dutton, Peter H.; Benson, Scott R. (Frontiers in Marine Science, 2016)
The dive behavior of gravid leatherback turtles (Dermochelys coriacea) was studied during the internesting interval in two western Pacific nesting regions: Papua Barat, Indonesia, and the Solomon Islands in 2006, 2007 and 2010. We used three types of dive data: time-at-depth data (Papua Barat: N = 4; Solomon Islands: N = 6), intermittent dive data (Papua Barat: N = 6) obtained from ARGOS satellite transmitters, and continuous dive data obtained from recovered semi-archival tags (Papua Barat: N = 1, Solomon Islands: N = 1). All dive data demonstrated that the leatherback turtles routinely dove to deep waters (around 150 m) throughout the internesting interval. The continuous dive data showed that turtles spent 37.3% of their time in routine deep dives and that they stayed in cold waters below the thermocline. Fine-scale monitoring (1-s interval, 0.5 m of resolution) suggested that these routine deep dives were not accompanied with any wiggles (up-and-down undulations in the depth profile) or flat-bottom phases, and they reached deep waters by gliding, which suggests that these dives may have served to conserve energy and/or to thermoregulate. Comparison with the dive behavior in other regions (Costa Rica, French Guiana, Grenada, Malaysia, and St. Croix) suggests that gravid leatherback turtles in all regions except French Guiana assume an energy-saving strategy during the internesting interval that involves gliding to or resting on the sea floor in colder water. The behavioral tactics (dive patterns) they use, however, differ because of bathymetric constraints.